Efektifitas Pendekatan Analisis Transaksional Berbasis Kato Nan Ampek Untuk Meningkatkan Komunikasi Interpersonal Siswa - Putri Yeni; Suwati Hendriani; Silvianetri Silvianetri; Masril Masril; Dasril Dasril (STKIP Andi Matappa, 2021)
The main problem in this research is the low interpersonal communication skills of students of MAN 3 Tanah Datar. The purpose of this study is to reveal empirical data about the effectiveness of group counseling based on Kato Nan Ampek transactional analysis to improve students' interpersonal communication skills in MAN 3 Tanah Datar. This type of research is quantitative research with experimental research methods, with a quasi experimental research design. Data Analysis Techniques Before the t test is carried out, the normality and homogeneity tests are first carried out with SPSS version 21.00. obtained quantitative data with a value of sig <0.05, namely sig = 0.000, this provides evidence that there is a significant difference in the scores for the level of interpersonal communication between the experimental group and the control group. This empirical evidence supports the results of this study, namely the Kato Nan Ampek-based Transactional Analysis group guidance is effective for improving interpersonal communication of students in MAN 3 Tanah Datar. It is recommended that guidance and counseling teachers in schools use transaskioanl analysis counseling to improve students' interpersonal communication skills provided that a counseling teacher already has experience and has done it according to good procedures